General Synthesis and Physicochemical Characterisation of a Series of Peptide‐Mimic Lysine‐Based Amino‐Functionalised Lipids. Issue 38 (9th August 2013) - Wölk, Christian; Drescher, Simon; Meister, Annette; Blume, Alfred; Langner, Andreas; Dobner, Bodo
Abstract A series of novel malonic acid diamides (second generation) with two long hydrophobic alkyl chains and an alkaline polar head group was synthesised and characterised as a new class of amino‐functionalised lipids. These peptide‐mimic lipids are suitable for polynucleotide transfer. The lipids bear a novel backbone consisting of a lysine unit and a malonic acid unit. Six different head‐group structures, which vary in size and number of amino groups that can be protonated, were attached to the backbone structure. Furthermore, different alkyl chains were used to build the lipophilic part (namely tetradecyl, hexadecyl, and oleyl). Phase transitions of the new compounds in aqueous dispersions at pH 10 were analysed and discussed in terms of head group and alkyl chain variations. The shape and size of the formed aggregates of selected lipid dispersions were investigated by dynamic light scattering and transmission electron microscopy.